Developing Brain Vital Signs: Initial Framework for Monitoring Brain Function Changes Over Time - Ghosh Hajra, Sujoy; Liu, Careesa C.; Song, Xiaowei; Fickling, Shaun; Liu, Luke E.; Pawlowski, Gabriela; Jorgensen, Janelle K.; Smith, Aynsley M.; Schnaider-Beeri, Michal; Van Den Broek, Rudi; Rizzotti, Rowena; Fisher, Kirk; et al. (Frontiers in Neuroscience, 2016)
Clinical assessment of brain function relies heavily on indirect behavior-based tests. Unfortunately, behavior-based assessments are subjective and therefore susceptible to several confounding factors. Event-related brain potentials (ERPs), derived from electroencephalography (EEG), are often used to provide objective, physiological measures of brain function. Historically, ERPs have been characterized extensively within research settings, with limited but growing clinical applications. Over the past 20 years, we have developed clinical ERP applications for the evaluation of functional status following serious injury and/or disease. This work has identified an important gap: the need for a clinically accessible framework to evaluate ERP measures. Crucially, this enables baseline measures before brain dysfunction occurs, and might enable the routine collection of brain function metrics in the future much like blood pressure measures today. Here, we propose such a framework for extracting specific ERPs as potential “brain vital signs”. This framework enabled the translation/transformation of complex ERP data into accessible metrics of brain function for wider clinical utilization. To formalize the framework, three essential ERPs were selected as initial indicators: 1) the auditory N100 (Auditory sensation); 2) the auditory oddball P300 (Basic attention); and 3) the auditory speech processing N400 (Cognitive processing). First step validation was conducted on healthy younger and older adults (age range: 22-82 years). Results confirmed specific ERPs at the individual level (86.81%-98.96%), verified predictable age-related differences (P300 latency delays in older adults, p<0.05), and demonstrated successful linear transformation into the proposed brain vital sign (BVS) framework (basic attention latency sub-component of BVS framework reflects delays in older adults, p<0.05). The findings represent an initial critical step in developing, extracting, and characterizing ERPs as vital signs, critical for subsequent evaluation of dysfunction in conditions like concussion and/or dementia.